التنبؤ بالفشل المالي وتقييم الملاءة المالية طويلة الأجل باستخدام نموذج التمان دراسة تطبيقية على قطاع النقل الجوي الإماراتي والاردني - الحراحشة, عادل محمد توفيق (جامعة الوادي - University of Eloued, 2018)
This study aims at identifying the solvency of Emirates Airline, Air Arabia and Royal Jordanian Airline using the Altman-Z-Score model, which consists of five ratios reflecting the different aspects of corporate activity. The study found that Air Arabia and UAE Air were able to Achieved good rates and be within the safe area in most years but failed to maintain these levels in the rest of the years, but the Royal Jordanian could not reach the safe rates during the years of study
مقال
Keywords: الملاءة المالية، الناتج المحلي الإجمالي، المنطقة الرمادية.